Relationship Between Ideal Cardiovascular Health and Disability in Older Adults: The Chilean National Health Survey (2009–10) (2017)
This study aimed to examine the relationship between disability and the American Heart Association metric of ideal cardiovascular health (CVH) in older adults from the 2009–10 Chilean National Health Survey. Data from 460 older adults were analyzed. All subjects were interviewed using the standardized World Health Survey, which includes 16 health-related questions and assesses the domains of mobility, self-care, pain and discomfort, cognition, interpersonal activities, vision, sleep and energy, and affect. A person who responds with a difficulty rating of severe, extreme, or unable to do in at least one of these eight functioning domains is considered to have a disability. Ideal CVH was defined as meeting the ideal levels of four behaviors (smoking, body mass index, physical activity, diet adherence) and three factors (total cholesterol, fasting glucose, blood pressure). Logistic regression analysis suggested that ideal physical activity reduces the odds of disability (odds ratio (OR) = 0.55, 95% confidence interval (CI) = 0.36–0.85). Moreover, participants with intermediate (3–4 metrics) (OR = 0.63, 95% CI = 0.41–0.97) and ideal (5–7 metrics) (OR = 0.51, 95% CI = 0.24–0.97) CVH profiles had lower odds of disability independent of history of vascular events and arthritis disease than those with a poor profile (0–2 metrics). In conclusion, despite the cross-sectional design, this study suggests the importance of promoting ideal CVH because of their relationship with disability. © 2017, Copyright the Authors Journal compilation © 2017, The American Geriatrics Society